Modernization of the Russian Automobile Road Network on the Base of Innovative Technologies. Part 2 - Evgeny A. Zhukov; Sergey V. Ilyin (Модернизация, инновация, развитие)
Purpose: the authors aim to show the reality of the decision of the actual task putted by the Russian President V.V. Putin to transport builders: two times increasing construction of automobile roads and to ground fundamental principles of the Russian automobile roads network technological modernization, allowing solving the modern requirements of automobile transport.Methods: in the present study the following methods were used: systemic approach, methods of social diagnosis, comparative analysis, method of expert evaluations, and method of statistical processing of information.Results: the short characteristic of modern development and technical level of the Russian automobile roads network as the important part of the automobile roads material-technical base is presented. Realization process of the actual task putted by Russian President V.V. Putin to transport builders: two times increasing construction of automobile roads is analyzed. The reality of decision this task due to modernization roads economy material-technical base on the base of innovative technologies and progressive world experience in the field of roads construction is scientifically proved.Conclusions and Relevance: in spite of losing now in decision of the actual task putted by Russian President V.V. Putin to transport builders: two times increasing construction of automobile roads, nevertheless the real possibilities to reach the important aim still remain. It may be done only due to scientifically grounded modernization of the roads economy material-technical base on the base of innovative technologies and progressive world experience in the field of roads construction.